Upaya Pemerintah Desa Dalam Meningkatkan Partisipasi Masyarakat Dalam Pembangunan Di Desa Aibura Kecamatan Waigete Kabupaten Sikka - Edwin Rafael; H.Rodja Abdul Natsir; Danar Aswim (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2023)
This research aims to obtain more in-depth information regarding the Government's efforts to increase community participation in development in Aibura Village, Waigete District, Sikka Regency. The type of research used in this research is qualitative research. This research was conducted in Aibura Village, Waigete District, Sikka Regency. This study used qualitative research methods. The data sources taken are primary data and secondary data. The subjects of this research were the Head of Aibura Village, Village Government Officials and the Community. The techniques used are interviews, observation and documentation. Data analysis techniques consist of data reduction, data presentation, and data verification. Based on the research results, it can be concluded that community participation in development in Aibura Village can be said to be quite good, it can be seen from the efforts made by the Government in developing the community, by carrying out development activities involving the community, carrying out Musrembang activities involving the community.